PLANNING RELOCATION OF PEOPLE FOR DEVELOPING SURFACE MINES IN DENSELY POPULATED AREAS: OPTIMIZATION OF MULTIPLE OBJECTIVES - ZAHIR, SAJJAD; SARKER, RUHUL (Asia-Pacific journal of operational research, 2011)
Surface mining, often adopted for exploiting natural resources all over the world, is a major subject of debate as it causes major environmental impacts. It not only adversely alters the landscape but it also seriously hampers the traditional living conditions of numerous inhabitants, who may be displaced against their wishes without receiving necessary compensation. In this paper, goal programming is combined with the analytic hierarchy process to determine optimal decisions for the planned relocation of people where surface mining may take place in a densely populated environment, while addressing multiple conflicting objectives. The combined approach is illustrated with a numerical example highlighting its usage in other decision problems.